Joan’s Neurotic Trends and Idealized Image in Margaret Atwood’s Lady Oracle - Umi Hanifah; Muh. Arif Rokhman (Lexicon, 2020)
This research attempts to figure out the development of neurosis in Joan Elizabeth Delacourt’s case, the leading character of Margaret Atwood’s Lady Oracle. It applies Karen Horney’s theory of neurosis as the basis to determine whether the main character of the novel is adequately portrayed as a neurotic person. This research focuses on four basic elements of neurosis: basic anxiety and hostility, neurotic trends, neurotic conflict, and idealized image. It begins with the analysis of Joan’s childhood and teenage experiences which are believed to be the primary step of her basic anxiety and hostility formation. The next part is Joan’s neurotic trends development which will be analyzed at the moment when she finally met her future husband, Arthur. Accordingly, neurotic conflict and idealized image appear to complete the evidences that Joan is a neurotic.